2019
DOI: 10.21203/rs.2.10457/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutritional status of tuberculosis patients, a comparative cross-sectional study.

Abstract: Background Each year, more than 13.7 million people became an active case of tuberculosis and more than 1.5 million cases of TB patient will die. The association between TB and malnutrition is bi-directional, TB leads the patient to malnutrition, and malnutrition increases the risk of developing active TB by 6 to 10 times. Improving the nutrition of individual greatly reduces tuberculosis. The aims of this study were to assess the nutritional status and determinants of underweight among TB patients.Methods A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…In our study we observed that the HDL level of DM and TB patients was at 34.17 mg/dl, the baseline HDL level of DM free TB patients was at 43.49 mg/dl. The nding was in line with the nding in Netherland [41], suggesting high malnutrition burdens in the study area [42].…”
Section: Discussionsupporting
confidence: 86%
“…In our study we observed that the HDL level of DM and TB patients was at 34.17 mg/dl, the baseline HDL level of DM free TB patients was at 43.49 mg/dl. The nding was in line with the nding in Netherland [41], suggesting high malnutrition burdens in the study area [42].…”
Section: Discussionsupporting
confidence: 86%
“…Two hundred sixty-nine studies were screened by title and abstract. Finally, only 20 papers were found to be eligible for full-text evaluation, and 11 studies [3,4,11,12,[14][15][16][17][19][20][21] that fulfilled the eligibility criteria were included in the final analysis ( Table 1, Fig. 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The sample size in each included study ranged from 43 to 1681 TB patients. However, except for a study done by Feleke et al [14] that screened 1681 TB patients for intestinal parasites, the sample size for each of the remaining 10 studies was below 300. To diagnose TB, most of the studies used smear microscopy while one study from Addis Ababa and the other study from northeast Ethiopia used Mycobacterial culture.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI less than 18.5 kg/m2 is considered underweight [11]. Compared with the study of Berhanu Elfu Feleke et al on 1681 patients with TB, underweight PTB patients accounted for 43.7% [13] of the total and the research in Indian by Rachel W. Kubiak et al on 919 active TB patients, the majority (61%) of TB patients were underweight [14]. These results provided an additional fact that high proportions of TB patients were malnourished.…”
Section: Discussionmentioning
confidence: 99%